Peran Guru Dalam Menanamkan Sikap Toleransi Siswa Melalui Pembelajaran PPKn Kelas VII Di MTS Raudhlatul Hasaniyah Kabupaten Probolinggo - Ani Sulianti; Didit Yulian Kasdriyanto; Febriyanto (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This study aims to describe the teacher's role in encouraging tolerance in students through learning at VII MTS Raudlatul Hasaniyah in the 2022-2023 academic year. This research methodology is based on a qualitative approach with case studies. The material for this research is an overview of the teacher's role in instilling tolerance in students, using interviews and observations as the main data and documentation as a support and complement to the data. The subjects of this research were school principals, teachers and student representatives of MTs Raudlatul Hasaniyah. After data collection, qualitative data analysis was carried out.The results of the study show that the role of Civics teachers in increasing student tolerance is good because they can direct well, provide motivation, guide and evaluate, and manage all existing resources in educational institutions to achieve the character of student goals. However, the program was not implemented optimally, because there were still some teachers who did not support or carry out their duties which resulted in some students not being tolerant values. Known supporting and inhibiting factors. The supporting factors are a clean environment, adequate facilities and infrastructure, teaching staff and student textbooks, while the inhibiting factors are the environment, choosing the wrong friends and the location where students live in remote areas. Civics teacher's solution to increase student tolerance is to hold extracurricular activities, clean up and class meetings. However, the solution proposed by the school principal and PPKn teachers has not been fully implemented because there are still students and teachers who do not participate in its implementation.